Evaluation of a novel transition support intervention in an adult eating disorders service: ECHOMANTRA. (19th May 2019) - Adamson, James; Cardi, Valentina; Kan, Carol; Harrison, Amy; Macdonald, Pam; Treasure, Janet
Abstract: Admissions and re-admissions for inpatient care for anorexia nervosa have been increasing. The aim of this study was to examine whether the transition from inpatient care to the community could be facilitated by supplementing usual treatment with ECHOMANTRA (transition interventions) for both patients and carers. A case series study was employed using a mixed-methods approach to measure the feasibility and efficacy of augmenting intensive hospital treatment with ECHOMANTRA. A consecutive series of consenting patients ( n =  31) and carers ( n =  21) were assessed on admission, discharge, and at 3 months follow-up. These outcomes were compared with audit data ( n =  152) previously collected (2007–2017). The length of stay for the ECHOMANTRA intervention group was 4.5 weeks less than the comparison group, and weight gain was 0.11 kg per week higher. Improvements in patient symptomology were sustained at follow-up. Thematic analysis of the feedback from both patients and carers suggests that the intervention is valued. Carer burden was reduced and their skills improved (both moderate size changes). In conclusion, both the acceptability and efficiency of inpatient care for anorexia nervosa may be improved by augmenting treatment to prepare for transition from inpatient care by giving support to both patients and their carers.